Violence risk: assessment and management - Webster, Christopher D. (Wiley, 2007)
Laws -- Philosophies -- Predictions -- Errors -- Disorders -- Psychopaths -- Studies -- Baserates -- Factors -- Debates -- Guides -- Retrospective analysis / Patricia Stefanowska, Christopher D. Webster, & Randy Starr -- Competitions -- Sex offenders / R. Karl Hanson -- Spousal assaulters / P. Randall Kropp -- Interventions -- Transitions / Mary-Lou Martin -- Teams -- Communications -- Experts -- Conclusions -- Questions